Filamin A expression predicts early recurrence of hepatocellular carcinoma after hepatectomy. (20th August 2017) - Donadon, Matteo; Di Tommaso, Luca; Soldani, Cristiana; Franceschini, Barbara; Terrone, Alfonso; Mimmo, Antonio; Vitali, Eleonora; Roncalli, Massimo; Lania, Andrea; Torzilli, Guido
Abstract: Background & Aims: Recurrence of hepatocellular carcinoma (HCC) after hepatectomy is very high. A predictive marker of early recurrence (ER) capable of personalizing follow‐up and developing a new target therapy would be beneficial. The overexpression of Filamin‐A (FLNA), a cytoskeleton protein with scaffolding properties, has recently been associated with progression in tumours. The aim of this study was to test the expression of FLNA in a cohort of patients operated for HCC. Methods: A retrospective cohort of patients who underwent hepatic resection at Humanitas Clinical and Research Center between January 2004 and December 2014 was analysed. FLNA was tested, using a tissue microarray, in the HCC and in the surrounding tissues. The endpoint was the role of FLNA expression in predicting ER of HCC after hepatectomy. Analyses were performed following the REMARK guidelines. Results: A total of 113 patients were considered. FLNA was expressed only in the tumoral tissue. Several variables, including T stage, tumour number, tumour size, type of viral hepatitis, type of hepatectomy and intra and peritumoral immune‐reactivity to FLNA were significantly associated with ER by univariate analysis. With multivariate analysis, only T stage (HR=2.108; P =.002), tumour number (HR=1.586; P =.023), intra‐tumoral (HR=2.672; P <.001) and peritumoral immune‐reactivity to FLNA (HR=2.569; P <.001), significantly correlated with ER. The logistic regression analysis revealed that advanced T stage (OR=2.985; P =.001), HCV‐infection (OR=1.219; P =.008) and advanced tumour grading (OR=2.781; P =.002) were associated with intratumoral FLNA immune‐reactivity. Conclusions: FLNA expression predicts recurrence of HCC after hepatectomy. This finding provides important insights that would help physicians to personalize follow‐up strategies.